Effect of sodium hypochlorite temperature and concentration on the fracture resistance of root dentin - Reem M. Barakat; Rahaf A. Almohareb; Munirah Alsuwaidan; Ebtihal Faqehi; Enas Alaidarous; Fahda N. Algahtani (BMC, 2024)
Abstract Background Sodium hypochlorite (NaOCl) is the most efficient root canal irrigant to date. The aim of this study was to compare the effect of NaOCl used at different temperatures and concentrations on the compressive strength of root dentin. Materials and methods Seventy-two extracted human single-canaled straight roots of comparable size and length were selected and randomly divided into six groups (n = 12): Group (A) served as a control with unprepared canals. The other groups were instrumented with rotary ProTaper Universal files up to size F3. Group (B) was irrigated with 1% NaOCl at room temperature, Group (C) with 1% NaOCl heated to 70 °C, Group (D) with 5.25% NaOCl at room temperature, and Group (E) with 5.25% NaOCl heated to 70 °C. Saline was used in Group (F). The roots were sectioned into 2-mm-thick disks that underwent compression testing using a universal testing machine. Data were analyzed using one-way ANOVA and post hoc Tukey tests. The significance level was set at p ≤ 0.05. Results A total of 255 disks were tested. The control group showed the highest compressive strength (p = 0.0112). However, this did not differ significantly from that of heated (p = 0.259) or unheated (p = 0.548) 1% NaOCl. There were no statistically significant differences between the groups of instrumented teeth. Conclusion Within the conditions of this study, irrigation with NaOCl at different concentrations and temperatures during root canal preparation did not affect the compressive strength of root dentin. Clinical Relevance: This study demonstrates that the use of NaOCl as a root canal irrigant is not associated with a clinically relevant decrease in root compressive strength, especially when compared to saline.